Wspólne motywy w dżatace Suwannahansa (Suvaṇṇahaṃsa) i bajce Ezopa o gęsi znoszącej złote jajka - Łozowska, Alicja (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
This paper analyzes the motif of the golden goose and of the goose (or hen) that laid golden eggs that appear in both the Buddhist Suvaṇṇahaṃsa-jātaka and one of Aesop’s fables. Common characteristics of these works are analyzed and the history of the golden goose in Indian literature from both pre-Buddhist and Buddhist times is presented, which indicates that the story has an Indian origin.